2024
DOI: 10.1186/s12871-024-02411-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of delayed tracheostomy on critically ill patients receiving mechanical ventilation: a retrospective cohort study in a chinese tertiary hospital

Jie Zhao,
Wei Zheng,
Nan-xian Xuan
et al.

Abstract: Objectives The timing of tracheostomy for critically ill patients on mechanical ventilation (MV) is a topic of controversy. Our objective was to determine the most suitable timing for tracheostomy in patients undergoing MV. Design Retrospective cohort study. Setting and participants One thousand eight hundred eighty-four hospitalisations received tracheostomy from January 2011 to December 2020 in a Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In a retrospective cohort study involving 1884 general intensive care unit patients, the patients were divided into subgroups based on their admission diagnoses, and tracheostomies performed within 7 days, between 7 and 14 days, and after 14 days were examined. That study found that delayed tracheostomy was associated with prolonged ICU stay, increased sedation requirements, and prolonged mechanical ventilation duration [21].…”
Section: Discussionmentioning
confidence: 94%
“…In a retrospective cohort study involving 1884 general intensive care unit patients, the patients were divided into subgroups based on their admission diagnoses, and tracheostomies performed within 7 days, between 7 and 14 days, and after 14 days were examined. That study found that delayed tracheostomy was associated with prolonged ICU stay, increased sedation requirements, and prolonged mechanical ventilation duration [21].…”
Section: Discussionmentioning
confidence: 94%
“…These findings coincided with data from a retrospective study by Zhao J et Al. [5], in which patients with late tracheotomy had a longer hospital stay of 39 days on average, p < 0.001 and in the cohort study of Fernanda Kazmierski Morakami et al [6] where patients with early vs. late tracheotomy had a shorter hospital stay (42 ± 32 vs. 52 ± 50 days, p < 0.001).…”
Section: Discussionmentioning
confidence: 97%